The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/adfm.202010638
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Enabled Low‐Noise Surface Chemistry for Multiplexed Sepsis Biomarker Detection in Whole Blood

Abstract: Affinity‐based electrochemical (EC) sensors offer a potentially valuable approach for point‐of‐care (POC) diagnostics applications, and for the detection of diseases, such as sepsis, that require simultaneous detection of multiple biomarkers, but their development has been hampered due to biological fouling and EC noise. Here, an EC sensor platform that enables detection of multiple sepsis biomarkers simultaneously by incorporating a nanocomposite coating composed of crosslinked bovine serum albumin containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 56 publications
(49 reference statements)
0
62
0
Order By: Relevance
“…Incorporating terminal amine groups in rGOx augments their interaction with polymer matrices and their distribution by altering their solubility and agglomeration, in addition to enhancing the physical, mechanical, thermal, and electrical stability of the composite via covalent linking of the amines by GA pyridine polymers. 16, 17 Indeed, when we compared the effects of amine-functionalized rGOx we used previously versus pentaamine-functionalized rGOx (prGOx), we found that the prGOx maintained a higher current density and lower peak-to-peak distance when measured immediately after coating or after incubating in 1% BSA for 1h or 1 day ( Fig. 1b ).…”
Section: Ultra-fast Deposition Of An Antifouling Coating On Ec Sensorsmentioning
confidence: 93%
See 2 more Smart Citations
“…Incorporating terminal amine groups in rGOx augments their interaction with polymer matrices and their distribution by altering their solubility and agglomeration, in addition to enhancing the physical, mechanical, thermal, and electrical stability of the composite via covalent linking of the amines by GA pyridine polymers. 16, 17 Indeed, when we compared the effects of amine-functionalized rGOx we used previously versus pentaamine-functionalized rGOx (prGOx), we found that the prGOx maintained a higher current density and lower peak-to-peak distance when measured immediately after coating or after incubating in 1% BSA for 1h or 1 day ( Fig. 1b ).…”
Section: Ultra-fast Deposition Of An Antifouling Coating On Ec Sensorsmentioning
confidence: 93%
“…To develop an efficient process flow for mass manufacturing, a nanocomposite coating method was developed using on-chip heating to facilitate rapid deposition of our previously described BSA/rGOx composite. 17 Clean gold electrodes were heated at 85 0 C with the nanocomposite material for 30 sec to 5 min, followed by washing in PBS immediately or after cooling down for 10 min. This ultra-rapid cross-linking mechanism results in creation of porous three dimensional (3D) molecular networks, and we were able to detect this reaction by measuring increase in absorbance at 265-270 nm (Supplementary Fig.…”
Section: Ultra-fast Deposition Of An Antifouling Coating On Ec Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reports on multiplexed sensors with PCT as one of the analytes are available in literature [48]. A lab-on-a-chip immunosensor array was reported for simultaneous detection of the pro-inflammatory markers PCT, interleukin-6 (IL-6) and C-reactive protein (CRP) using a cyclooctene (TCO)-tetrazine (Tz)-horse radish peroxidase (HRP) assembly [49]. The ratio of TCO-HRP and Tz-HRP was optimized to achieve adequate chemiluminescent response for the different markers that are present in varying levels in blood.…”
Section: Multiplexed Sensorsmentioning
confidence: 99%
“…Here we demonstrate the sensitivity, repeatability and specificity of the GFET biosensors for the detection of pure proteins. The next stage of the study will be to investigate the sensor response using real patient samples (such as serum, plasma, or blood), stability and storage of the sensors (Teixeira et al, 2014;Leva-Bueno et al, 2020;Zupančič et al, 2021). Thus, GFET biosensors offer a unique route towards the development of vitally needed diagnostic platform for AD.…”
Section: Introductionmentioning
confidence: 99%